Exposure of Mycobacteriodes abscessus clones to mucin affects bacterial phenotype - Amy Leestemaker-Palmer; Tiffany Ong; Luiz E Bermudez (Scientific Reports)
Abstract In the past 20 years infections caused by Mycobacterioides abscessus have become increasingly common in patients with chronic lung conditions. The microorganisms are also resistant to a number of antibiotic classes, making treatment challenging. To begin understanding how the bacterium adapts to the lung environment, pure colonies of M. abscessus strain 19,977 were grown in 7H9 broth with or without mucin over 30-day intervals for 6 months and analyzed for colony morphology, 7 day-growth curves, the ability to form biofilms after 14 days, and the susceptibility to antibiotics determined using previous published methods. In presence of mucin by month 3 the non-replicating stage of growth occurred by day 3, compared to earlier months. Similar characteristics were seen in colonies grown in absence of mucin by month 5. During biofilm formation, the amount of protein in the matrix started to decrease at month 3 between day 7 and day 14, with progressive overall biomass decreased in month 6. Mucin exposed clones had less of this decrease between day 7 and day 14 compared to clones naïve to mucin. The number of bacteria in the biofilms were similar in all 6 months in 7H9 medium and 7H9 with mucin. Some of the strains increased the amount of carbohydrates in the biofilm matrix overtime while others exported more DNA, the matrix containing large amounts of it. The presence of mucin was associated with increased antibiotic resistance to amikacin, 5-fold increase of MIC in 7 out of 8 strains evaluated. Some of the colonies transitioned from smooth to rough morphotypes, again indicating the influence of different environments. Overall, M. abscessus phenotype changes overtime influenced by mucin, an important component in the host lung environment. Bacteria clones arrested growth, produced different biofilms compositions, increased the resistance to antibiotics, and some changed the cell wall surfaces. These observations have direct implications in virulence and the response of the pathogen to treatment.